2004
DOI: 10.1167/iovs.03-1230
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Transient Pupillary Light Reflex inRpe65−/−Mice and Humans with Leber Congenital Amaurosis

Abstract: Pupillometry was used to quantify visual impairment and to probe transmission of retinal signals to higher nervous centers in a murine model of LCA and in patients with LCA. Mouse results were consistent with a dominant role of image-forming photoreceptors driving the early phase of the TPLR when elicited by short-duration stimuli. The objective and noninvasive nature of the TPLR measurement, and the observed post-treatment change toward normal in the animal model supports the notion that this may be a useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 59 publications
7
91
0
Order By: Relevance
“…The data presented here suggest that the loss of RPE65, or its defects, may also be detrimental (at least partially) to the non-image-forming visual functions in these LCA patients. The rod-cone vision of rpe65 Ϫ/Ϫ mice can be rescued by exogenous 9-cis-retinal or 11-cis-retinal, suggesting a potential therapy for restoring vision in these LCA patients (18,24,25,36). The same may apply to the non-image-forming visual functions.…”
Section: Discussionmentioning
confidence: 93%
“…The data presented here suggest that the loss of RPE65, or its defects, may also be detrimental (at least partially) to the non-image-forming visual functions in these LCA patients. The rod-cone vision of rpe65 Ϫ/Ϫ mice can be rescued by exogenous 9-cis-retinal or 11-cis-retinal, suggesting a potential therapy for restoring vision in these LCA patients (18,24,25,36). The same may apply to the non-image-forming visual functions.…”
Section: Discussionmentioning
confidence: 93%
“…There were no significant changes in sensitivity in the control eye. Pupillary reactions in the dark (21,22) also indicated increased light sensitivity in the study eyes of patients 2 and 3; this method showed no detectable change in sensitivity in the study eye of patient 1 or the control eyes of all three patients (Fig. S2).…”
Section: Human Gene Therapy Surmounts Biochemical Blockade In Rpe65-lcamentioning
confidence: 84%
“…All homozygous patients showed a complete loss of ERG responses and an abnormal pupillary reflex. However, a recordable reflex could be obtained in some of the homozygotes, suggesting that pupillometry may be one objective means of assessing and monitoring visual function in these patients as well as in patients who may benefit from future gene therapy [1]. In contrast, heterozygous patients showed normal visual function, ERG and pupillometry.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a retinol ester-binding protein that plays an important role in the vitamin A cycle, being necessary for the conversion to 11-cis retinal [7], the chromophore of the visual pigments. 1 Mice and dogs lacking RPE65 gene (knock-out model) have been developed and studied [22,28]. Histopathologic examinations of the diseased eyes from these animal models have revealed decreased accumulation of lipofuscin [11] and increased accumulation of retinyl esters in the RPE [16].…”
Section: Introductionmentioning
confidence: 99%